Further Reflections on the Methodology of Chinese Philosophical Research—Starting from Cashing in the "Bank-Note of Ideas". Issue 2 (3rd April 2017) - Shaoming, Chen
EDITOR'S ABSTRACT: This paper compares speculative or textbook philosophy with kite flying risking to lose touch with the topic of reflection. The alternative that Chen defends here is a more experience-grounded, concrete, and imaginary reflection on less often discussed ideas and on allegories. He carves out this approach from four related disciplinary methodologies: the "philological" focus on textual matters, the "history of thought" focusing on past eras, "scholastic history" (a term from Qian Mu) connecting past ideas with their future, and "history of philosophy" immediately searching Chinese equivalents for Western notions. The experience that Chen stresses is that of the text's original authors and later interpreters. This approach can also leads toward universal insights and the pleasure of an unending interpretive dialogue.